IL-17A Enhances Microglial Response to OGD by Regulating p53 and PI3K/Akt Pathways with Involvement of ROS/HMGB1 - Zhang, Bin; Yang, Ning; Mo, Zhi-Ming; Lin, Shao-Peng; Zhang, Feng (Frontiers in Molecular Neuroscience, 2017)
Cerebral ischemia-reperfusion injury (IRI) has a complex pathogenesis, and interleukin-17 (IL-17) is a newly identified class of the cytokine family that plays an important role in ischemic inflammation. An oxygen-glucose deprivation (OGD) model showed that IL-17A expression was significantly up-regulated in microglial cells. After IL-17A siRNA transfection, the inhibition of proliferation, and the increased apoptosis in microglial cells, induced by OGD/reperfusion, was improved, and the elevation of Caspase-3, Caspase-8, Caspase-9, and poly ADP ribose polymerase (PARP) activities was inhibited. Mass spectrometry demonstrated that IL-17A functioned through a series of factors associated with oxidative stress and apoptosis and regulated Caspase-3 activity and apoptosis in microglial cells via the p53 and PI3K/Akt signaling pathways. IL-17A, HMGB1, and ROS were regulated mutually to exhibit a synergistic effect in the OGD model of microglial cells, but the down-regulation of IL-17A or HMGB1 expression did not completely inhibit the production of ROS. These findings demonstrated that ROS might be located upstream of IL-17A and HMGB1 so that ROS can regulate HMGB1/IL-17A expression to affect the p53 and PI3K/Akt signaling pathways and therefore promote the occurrence of apoptosis in microglial cells. These findings provide a novel evidence for the role of IL-17A in ischemic cerebral diseases.